Women and the "third way" commentary by Zainab Salbi. (Journal of International Affairs, 2013)
"The Middle East has become a key place in the battle to negotiate the role of women. Indeed, during the Arab Spring revolutions, women actively and publicly participated. This was a striking feature, as many of the countries in the region had and continue to actively regulate the private and public lives of women. As revolution gives way to transition, questions remain as to how these newfound realities will incorporate gender in the state-building and reintegration processes, as well as in economic development and the rule of law. Zainab Salbi, founder of Women for Women International, a grassroots development organization that has helped women globally access social and economic opportunities, shares with the Journal her reflections on the future. Having interviewed women activists over the past few months, Salbi explores the vital role of women activists in the revolutions, and argues that we cannot talk about the stability and future of these countries without recognizing the "Third Way" and the moderating and inclusive voices of these women."